TINJAUAN YURIDIS TERHADAP PUTUSAN LEPAS DARI SEGALA TUNTUTAN HUKUM - Maimunah Maimunah (Journal of Law ( Jurnal Ilmu Hukum ), 2019)
ABSTRACTThe purpose of this research is to find out more about the verdicts free from all lawsuits using normative juridical research methods. It was concluded that: 1. Appeals that can be made in a ruling free from all lawsuits. 2. In ruling a verdict off all lawsuits the judge is very careful in taking his decision and is guided by applicable laws and laws. The verdict handed down by a judge for a case which is examined and tried is the result of an analytical process of the legal facts associated with the rule of law and is complemented by legal arguments.Keywords: Verdict, Lawsuits